A Citation Analysis Study of the 50 Most-Cited Articles on the Achilles Tendon. Issue 4 (November 2022) - Bernasconi, Alessio; Sgadari, Arianna; Izzo, Antonio; Marasco, Domenico; Lintz, Francois; Netto, Cesar de Cesar; Mariconda, Massimo; Smeraglia, Francesco
Category: Other; Basic Sciences/Biologics Introduction/Purpose: Achilles tendon injuries represent one of the most common reasons of referral to orthopaedic surgeons. The purpose of this study was to determine the 50 most-cited articles on Achilles tendon pathologies in order to outline their characteristics, examine trends in publication and evaluate the correlation between citations and the quality of evidence. Methods: We searched Web of Science papers with the single keyword 'Achill*'. We identified and analyzed the top 50 most- cited articles and abstracted their characteristics. The methodological quality was assessed using the modified Coleman Methodology Score (mCMS). The correlation between the number of citations, the citation rate (citations/y), the impact factor of the journal for the year 2020 (JIF), the year of publication, the Level of Evidence (LoE), the type of study (tendon rupture, acute tendinopathy, chronic tendinopathy), the sample size and the mCMS was assessed through multiple bivariate analyses (Pearson or Spearman correlation coefficient). Results: Mean number of citations (+-SD) was 244 +- 88.8 (range, 657 to 157), with a total number of citations of 12.194 and a mean citation rate of 12.6 +- 5.4 (range, 28 to 3). The mean impact factor for the ten journals in which the 50 manuscripts were published was 5.1. The citation rate correlated with the number of citations (R=0.56, p<0.001), the year of publication (R=0.60, p<0.001) and the LoE (R=-0.37, p=0.022), but not with the citation rate (p=0.15). The year of publication correlated with the LoE as well (R=-0.43, p=0.008). Also, the quality of studies (in terms of mCMS) correlated with the impact factor of journals (R=0.35, p 0.03) and with the LoE (R=-0.48, p=0.003). Only 20 out of 39 primary studies (51%) had a prospective and comparative design, while 19 studies (48%) were classified as of poor quality (< 50 points using the mCMS). Conclusion: Most-cited articles in the field of Achilles tendon injuries have generally been published on high-impact journals. Although the impact factor positively correlates with the quality of studies, their methodology is poor in almost half of cases. The average Level of Evidence provided by studies and their citation rate are both significantly increasing over time. Citation-based indicators do not represent robust measures of quality in studies dealing with Achilles tendon pathologies.